THE USE OF BAAMBOOZLE GAMES TO TEACH VOCABULARY - Zanuar, Muhammad Rifqi; Daristin, Pipit Ertika; Maisaroh, Ummi (Program Studi Pendidikan Bahasa Inggris,, Fakultas Ilmu Pendidikan, Universitas Hasyim Asy'ari, 2024)
There are a lot of challenging problems in education today that are connected to societal change and technology advancement. In the present era, the number of digital natives, or at least second-generation traditions, is growing. These are people that consider their environment to be the digital one they have been a part of since birth. Many research investigations have demonstrated how game-based learning encourages students to actively participate in the classroom because it makes them feel good. The purpose of this study is to investigate how well Bamboozle works for teaching vocabulary in English. This study is a literature review. Teaching English in the classroom with Baamboozle is interesting. By using a gamification technique, such as Baamboozle games, the quick advancements in technology can produce a competitive environment that can be used inside the classroom